Lung Function Assessment by Impulse Oscillometry in Adults [Corrigendum] - Porojan-Suppini N (Dove Medical Press, 2021)
Porojan-Suppini N, Fira-Mladinescu O, Marc M, Tudorache E, Oancea C. Ther Clin Risk Manag.2020;16:1139–1150. On page 1146, Other Diseases – Graft Function, Lung Transplant, Sickle-Cell Disease section, “A recent Chinese study, performed on 156 lung-transplanted patients, shows that Oscillometry identified physiological changes associated with grade 2 acute cell rejection that were not observed on spirometry and it’s usefor graft monitoring after a lung transplant.100” should read “A recent study, performed on 156 lung-transplanted patients, shows that Oscillometry identified physiological changes associated with grade 2 acute cell rejection that were not observed on spirometry and it’s use for graft monitoring after a lung transplant.100” The authors apologize for this error. Read the original article